In Reply: Study Protocol of Early-Intervention Acupuncture Analgesia Among Patients With Suspected Acute Renal Colic in Emergency Department [Response to Letter] - Wang X; Cao Y; Liu CZ; Tu JF; Qu ZC (Journal of Pain Research)
Xiao Wang,1 Ying Cao,2 Cun-Zhi Liu,1 Jian-Feng Tu,1 Zhi-Cheng Qu2 1School of Acupuncture-Moxibustion and Tuina, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 2Emergency Department, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Jian-Feng Tu, School of Acupuncture-Moxibustion and Tuina, Beijing University of Chinese Medicine, No. 11, Bei San Huan Dong Lu, Chaoyang District, Beijing, 100029, People’s Republic of China, Email tujianfeng1@126.com Zhi-Cheng Qu, Emergency Department, Beijing Hospital of Traditional Chinese Medicine, Capital Medical University, 23 Meishuguanhou Street, Dongcheng District, Beijing, 100010, People’s Republic of China, Email qzhch0824@163.com